Cause of intrauterine and neonatal death in twin pregnancies (CoDiT): development of a novel classification system. (16th June 2020) - Gulati, N; Mackie, FL; Cox, P; Marton, T; Heazell, AEP; Morris, RK; Kilby, MD
Abstract : Objective: Twin pregnancies have a significantly higher perinatal mortality than singleton pregnancies. Current classification systems for perinatal death lack twin‐specific categories, potentially leading to loss of important information regarding cause of death. We introduce and test a classification system designed to assign a cause of death in twin pregnancies (CoDiT). Design: Retrospective cross‐sectional study. Setting: Tertiary maternity unit in England with a perinatal pathology service. Population: Twin pregnancies in the West Midlands affected by fetal or neonatal demise of one or both twins between 1 January 2005 and 31 December 2016 in which postmortem examination was undertaken. Methods: A multidisciplinary panel designed CoDiT by adapting the most appropriate elements of singleton classification systems. The system was tested by assigning cause of death in 265 fetal and neonatal deaths from 144 twin pregnancies. Cause of death was validated by another obstetrician blinded to the original classification. Main outcome measures: Inter‐rater, intra‐rater, inter‐disciplinary agreement and cause of death. Results: Cohen's Kappa demonstrated 'strong' (>0.8) inter‐rater, intra‐rater and inter‐disciplinary agreement (95% CI 0.70–0.91). The commonest cause of death irrespective of chorionicity was the placenta; twin‐to‐twin transfusion syndrome (TTTS) was the commonest placental cause in monochorionic twins and acute chorioamnionitis in dichorionic twins. Conclusions: This novel classification system records causes of death in twin pregnancies from postmortem reports with high inter‐user agreement. We highlight differences in aetiology of death between monochorionic and dichorionic twins. Tweetable abstract: New classification system for #twin cause of death 'CoDiT' shows high rater agreement. Tweetable abstract: New classification system for #twin cause of death 'CoDiT' shows high rater agreement.